Study of The Use of Bamboo as a Construction Material for Accommodation in The Tourism Industry - Md fadzil, Nur farina maisarah binti; Saji, Nurdalila (Progress in Engineering Application and Technology, 2021)
Bamboo has been used as a building material for a long time, most traditional houses in Southeast Asia have used bamboo as a construction material, however, bamboo has its disadvantage and has its own shelf life. This paper is aimed to determine the level of suitability of the use of bamboo as a construction material for accommodation and to examine the comfort for visitors staying at Tadom Hill Resort, Banting, Selangor. This study only focuses on walls, foundations, and floors in accommodation at Tadom Hill Resorts. The data collected from questionnaires which are distributed to 40 respondent which is the visitor who has visited Tadom Hill Resorts. From the data analysis, some of the respondents disagree with the use of bamboo as a construction material for their accommodation. Next, the types of bamboo used by Tadom Hill Resort for accommodation there are Semantan, Semeliang, and Betung bamboo types. Tadom Hill Resorts also maintains the accommodation by painting using shellac and bamboo vinegar. According to the management of Tadom Hill Resorts, the bamboo used can last for about 20 years if there are proper maintenance and care. Thus, the information related to the uses of bamboo and the fact of bamboo need to be exposed to the visitors.